Transient Places: The Public Benefits of Short-Term Artist-Led Spaces - Finan, Shane (Irish Journal of Arts Management and Cultural Policy, 2014)
This paper explores the role of transient artist-led spaces in Ireland, and looks to discern whether shorter-term initiatives may become a strong model for sustaining artist-led activity in Ireland. It focuses on identity of local places for individuals and societies, and the role that artist-led initiatives have in altering this identity.